Efficacy of Neoadjuvant Targeted Therapy in Treatment of Patients with Localised Clear-Cell Renal Cell Carcinoma - O. A. Voylenko; O. E. Stakhovsky; I. V. Vitruk; O. A. Kononenko; M. V. Pikul; S. L. Semko; E. O. Stakhovsky (Advances in Urology)
Aim. This study aimed to evaluate the efficacy of neoadjuvant targeted therapy (TT) in patients with localised clear-cell renal cell carcinoma (RCC). Materials and Methods. A special randomised trial was planned and conducted by the Research Department of Plastic and Reconstructive Oncology in the National Cancer Institute of Ukraine for testing the clinical efficacy of neoadjuvant TT in the treatment of clear-cell localised RCC, and the primary endpoint was tumour response evaluation after TT. The secondary endpoints included evaluation of dependence between the use of neoadjuvant TT and the probability of partial nephrectomy and the correlation between tumour size, stage, remaining functioning parenchyma volume, and response to systemic therapy. Results. Overall, 118 patients met the inclusion criteria and were randomly assigned to receive combined treatment or surgery alone. The percentage of tumour regression ranged from 0% to 60%, and the median was (95% confidence interval) 20.5 ± 14.3 (16.8–24.3%). Most of the patients had a slightly positive response to TT (3%–29% decrease in tumour size); n = 44 (76.9%) cases. Partial response by the Response Evaluation Criteria in Solid Tumours, version 1.1, was observed in 14 (24.1%) patients and reached a maximum of 60% regression. Tumour reduction in the neoadjuvant TT group allowed kidney preservation in 53 (91.4%) patients. In the control group, the number of organ-sparing procedures was significantly lower (n = 20, 33.3%). The statistical difference was relevant (x2 = 42.1; p<0.001). Conclusion. The positive results of neoadjuvant TT obtained in our study indicate the clinical validity of combined treatment in patients with localised RCC.